Storytelling dan Movie Discussion sebagai Strategi untuk Meningkatkan Keterampilan Berbicara Bahasa Inggris di SMA Negeri 12 Makassar (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to analyze the effectiveness of storytelling and movie discussion methods in improving students' English speaking skills at SMA Negeri 12 Makassar. The background of this research departs from the low active participation and courage of students in using oral English in class. The method used is a hands-on practice-based learning approach, where students are asked to tell stories orally and discuss short films in English. The research subjects consisted of 36 students in grades XI-3 who were involved in interactive learning activities with the support of visual media and group discussions. The results of the study showed a significant improvement in several aspects of speaking skills, namely fluency in speaking, mastery of vocabulary, pronunciation, and students' confidence in conveying ideas and opinions. In addition, this method also encourages the development of critical thinking skills, creativity, and cooperation between students in a fun and participatory learning atmosphere. Storytelling activities allow students to express themselves freely and in a structured way, while movie discussions facilitate understanding of cultural context and authentic use of language. Thus, the application of storytelling and movie discussion methods has proven to be effective as an innovative learning strategy in developing students' English speaking skills at the high school level. This study recommends the integration of these methods in the English language learning curriculum to improve the overall quality of students' oral communication.